Bilan lipidique chez les diabétiques type II et contribution à une phytothérapie par l’Atriplex halimus. L (Guettaf) - Benzait, Asma; PBennama, Fatima (My University, 2016)
In diabetes, lipid abnormalities are frequent and pronounced and is an important factor implicated in the increased cardiovascular risk, especially in type 2 diabetics Atriplexhalimus L appears to be a plant rich in secondary metabolites : flavonoids, alkaloids, sterols, polyterpenes, tannins and terpenoids, the plant is widely used in traditional medicine and in food as a very good source of proteins in the Sahara region of Algeria .Objective of our work was to perform a phytochemical screening of different extracts of A. halimus L and evaluate the antihyperglycemic effect in the medium term (15 days), after daily oral administration of a herbal tea of Atriplexin type II diabetics and followed by the analysis of lipidbefore and after treatment. Our results show that A. halimus decreased significantly blood sugar, cholesterol, lipid and triglyceride serum levels in type 2 diabetics. This work remains preliminary on the actual mechanism by which interacts A. halimus reducing hyperglycemia and hypertriglyceridemia. Therefore, the realization of a later study of animal species is crucial. This will be rewarding and can lead us to the discovery of new substances with antidiabetic activity.
Keywords: Atriplexhalimus; diabete; glycémie; cholesterol; triglycerides; diabetes; blood sugar; triglycerides.; مرض السكري; الدھون الثل; السكر; الكولسترول